Analysis of the Factors that Affect the Capital Expenditure of the Central Java Provincial Government - Khoirotunnisa, Nabila; Mujiyati, Mujiyati (Prosiding University Research Colloquium, 2022)
Research on capital expenditure concludes the result of the pros and cons, therefore research on capital expenditure will always attract attention even though reasearchers use varied variables. The purpose of this study is to analyze and examine the effect of Local Own-Source Revenue, General Allocation Fund, Revenue Sharing Fund, and Gross Regional Domestic Product on Capital Expenditures. The research method used is a quantitative method. The population in this study is The Regency/City of Central Java Province for the 2017-2019 period. This study uses the saturation sampling method so total sample is 35 consisting of 29 district and 6 cities. The data of this study were tested using multiple linear regression models. The results of this study indicate that Local Own-Source Revenue has a significance value of 0,000 < 0,05 affecting Capital Expenditures, which means H1 is acceptable. The General Allocation Fund has a significance value of 0,000 < 0,05 affecting Capital Expenditures, which means H2 is acceptable. Revenue Sharing Fund has a significance value of 0,019 < 0,05 affecting Capital Expenditures, which means H3 is acceptable. Gross Regional Domestic Product has a significance value of 0,677 > 0,05 does not affect Capital Expenditure, which means H4 is rejected.